O empreendedorismo social no contexto rural: um estudo em organizações do interior da Paraíba - Maciel, Helltonn Winícius Patrício (2017)
This study aimed to analyze the Social Entrepreneurship in the Rural Context in organizations in the countryside of Paraíba. To achieve this goal, the following specific objectives were established: i) characterize social entrepreneurship in the rural context; Ii) identify determining factors in the configuration of social entrepreneurship in the rural context; Iii) identify links between social entrepreneurship and the traits of solidarity entrepreneurship in the rural context; and iv) delimit the elements that characterize the solidarity entrepreneurship in the rural context. Therefore, a review of literature on a critical analysis of economic entrepreneurship was carried out, the question of citizenship in a historical-conceptual perspective, the Social Entrepreneurship (ES) as concept and unfolding, as well as from bibliometric studies, the possible links between the ES and citizenship, and, finally, solidarity entrepreneurship and possible articulations with the ES, since its peculiar aspects are closer to the empirical context studied. The analysis process was guided by the interpretative paradigm and adopted a qualitative approach, since the discussion of the theme was constructed from the analysis of narratives from presidents and participants of organizations originated or belonged to the rural context. The emerged categories, classified in this work as tension mediators, complemented the analysis of social entrepreneurship in the investigated environment in some aspects: the role of the association leader, the community space, the family succession and the role of public agents. The main contributions of this study were: a) the elaboration of a continuum of social entrepreneurship, which presents in an integrated way several unfoldings of the phenomenon and situates one that was evidenced from the empirical studies developed; b) the identification that Solidarity-based Entrepreneurship in the Rural context (ESR) is a phenomenon that dialogues with other variations of the central phenomenon studied, so that we can understand it as a combination of perspectives on the theme, adding as factors of distinction the influence of the stress mediators that play a major role in the (non) development of ESR; c) the elaboration of a framework of reference for a better understanding of the studied phenomenon, which presents the links of the phenomenon itself with elements of other perspectives of social entrepreneurship. The theoretical novelty is also realized in the way the phenomenon is presented, which was not seen in the specific literature related to the subject. So this research offers a contribution that can lead to the development of new reference structures.